DNA methylation of ANKK1 and response to aripiprazole in patients with acute schizophrenia: A preliminary study. (May 2018) - Miura, Itaru; Kunii, Yasuto; Hino, Mizuki; Hoshino, Hiroshi; Matsumoto, Junya; Kanno-Nozaki, Keiko; Horikoshi, Sho; Kaneko, Haruka; Bundo, Miki; Iwamoto, Kazuya; Yabe, Hirooki
Abstract: Epigenetic modification including DNA methylation may affect pathophysiology and the response to antipsychotic drugs in patients with schizophrenia. The objective of the present study was to investigate the effect of the DNA methylation of ANKK1 (ankyrin repeat and kinase domain containing 1) on the response to aripiprazole and plasma levels of monoamine metabolites in antipsychotic-free acute schizophrenia patients. The subjects were 34 Japanese patients with schizophrenia who had been treated with aripiprazole for 6 weeks. Comprehensive DNA methylation of ANKK1 was determined using a next-generation sequencer. DNA methylation levels at CpG site 387 of ANKK1 were higher in responders to treatment with aripiprazole and correlated with the changes in Positive and Negative Syndrome Scale scores, although the associations did not remain significant after Bonferroni correction. In responders, methylation at all CpG sites was significantly correlated with plasma levels of homovanillic acid (r = 0.587, p = 0.035) and 3-methoxy-4hydroxyphenylglycol (r = 0.684, p = 0.010) at baseline. Despite our non-significant results after multiple correction, our preliminary findings suggest that methylation levels at CpG site 387 of ANKK1 may be associated with treatment response to aripiprazole. Furthermore, methylation of ANKK1 may affect dopaminergic neural transmission in the treatment of schizophrenia, and may influence treatment response. Caution is needed in interpreting these findings because of the small sample size, and further studies are needed to confirm and expand our preliminary results.